Analysis Study of the Problems of Arabic Language Learning at Junior High School - yuswandi; Hilmi, Danial (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This study aims to analyze the problems in Arabic language learning at MTs Nurul Falah Pamekasan. The focus of the research is to identify the challenges encountered in the teaching and learning process of Arabic and to provide appropriate solutions to address them. The issues found include various obstacles in Arabic language learning that encompass both internal and external factors, from both students and teachers, such as students' diverse backgrounds, teachers' limited abilities, and the lack of participation and response from students during the lessons. The research employs a descriptive qualitative methodology using Miles and Huberman's analytical approach, which consists of data collection, data reduction, data presentation, and conclusion drawing. Data were gathered through interviews, observations, and documentation from various stakeholders, including teachers and students at MTs Nurul Falah Pamekasan. The findings show that the main problems in Arabic language learning at this school include: (1) general issues such as an imbalanced teacher-student ratio and differences in students' language proficiency levels; (2) specific problems related to Arabic, particularly in grammar rules and writing; (3) individual student problems related to their diverse social, cultural, and educational backgrounds; and (4) teacher-related problems, such as the lack of expertise in Arabic and limited interest in attending professional development training. The proposed solutions include improving Arabic literacy among teachers, teaching grammar in accordance with students' abilities, and providing continuous training for teachers.